Efeitos das vivências em sexualidade na autoestima e na qualidade de vida de pessoas idosas. - Vitório de Souza Júnior, Edison; Pires Cruz, Diego; da Silva Filho, Benedito Fernandes; Brito Infante, Lucas Dias; Souza Rosa, Randson; dos Santos Silva, Cristiane; Reis Siqueira, Lais; Namie Okino Sawada (Anna Nery School Journal of Nursing / Escola Anna Nery Revista de Enfermagem, 2022)
Objective: to analyze the effects of sexuality on older adults’ self-esteem and quality of life. Method: a cross-sectional, web survey, analytical and observational study developed with 519 aged individuals, who filled out four instruments for data collection. The participants were recruited using a non-probability convenience sampling technique. The analysis was performed using the Mann-Whitney test, Spearman’s correlation and Structural Equation Modeling, with a 95% confidence interval. Results: among the sexuality dimensions, the sexual act had a weak effect on self-esteem (SC=0.186; p=0.007) and moderate on quality of life (SC=0.326; p<0.001). The affective relationships dimension had a weak effect both on self-esteem (SC=0.204; p=0.006) and on quality of life (SC=0.186; p=0.03). Finally, the physical and social adversity dimension had a moderate effect both on self-esteem (SC=0.276; p<0.001) and quality of life (SC=0.358; p<0.001). Conclusion: it was found that all the sexuality dimensions exerted positive and significant effects on the participants’ self-esteem and quality of life.